A multi-centre cohort study shows no association between experienced violence and labour dystocia in nulliparous women at term - Dykes Anna-Karin; Dejin-Karlsson Elisabeth; Finnbogadóttir Hafrún (BMC, 2011)
Abstract Background Although both labour dystocia and domestic violence during pregnancy are associated with adverse maternal and fetal outcome, evidence in support of a possible association between experiences of domestic violence and labour dystocia is sparse. The aim of this study was to investigate whether self-reported history of violence or experienced violence during pregnancy is associated with increased risk of labour dystocia in nulliparous women at term. Methods A population-based multi-centre cohort study. A self-administrated questionnaire collected at 37 weeks of gestation from nine obstetric departments in Denmark. The total cohort comprised 2652 nulliparous women, among whom 985 (37.1%) met the protocol criteria for dystocia. Results Among the total cohort, 940 (35.4%) women reported experience of violence, and among these, 66 (2.5%) women reported exposure to violence during their first pregnancy. Further, 39.5% (n = 26) of those had never been exposed to violence before. Univariate logistic regression analysis showed no association between history of violence or experienced violence during pregnancy and labour dystocia at term, crude OR 0.91, 95% CI (0.77-1.08), OR 0.90, 95% CI (0.54-1.50), respectively. However, violence exposed women consuming alcoholic beverages during late pregnancy had increased odds of labour dystocia, crude OR 1.45, 95% CI (1.07-1.96). Conclusions Our findings indicate that nulliparous women who have a history of violence or experienced violence during pregnancy do not appear to have a higher risk of labour dystocia at term, according to the definition of labour dystocia in this study. Additional research on this topic would be beneficial, including further evaluation of the criteria for labour dystocia.